PCB concentrations in sediments from the Gulf of Nicoya estuary, Pacific coast of Costa Rica - Alison L Spongberg (Revista de Biología Tropical, 2004)
Thirty-one sediment samples collected from 1996-2003 from the Gulf of Nicoya estuary on the north- western coast of Costa Rica, have been obtained for PCB analyses. This is part of the first study to evaluate the PCB contamination in coastal Costa Rica.Overall, the concentrations are low, especially when compared to sediments from more temperate climates and/or sediments from more heavily industrialized areas. Values average less than 3 ng/g dw sediment, however, a few samples contained up to 7 ng/g dw sediment. Sediments with the highest concentrations were located in the Punta Morales area, where muds were sampled from among mangrove roots. The Puntarenas samples had surprisingly low PCB concentrations, likely due to their sandy lithology. The congener distribution within the majority of the samples showed signs of either recent sources or lack of degradation. However, a few sites, specifically some of the inter-gulf islands and more remote samples had congener distributions indicative of airborne contaminants and/or degradation. Considering the presence of air-borne PCBs in the Gulf of Papagayo to the north, the lack of airborne PCBs and more varied congener distribution in the Gulf of Nicoya estuary was surprising Se analizó los bifenilos policlorados (PCB) en 31 muestras de sedimentos colectadas entre 1996 -2003 en el estuario del Golfo de Nicoya, costa noroeste de Costa Rica. Esto es parte de un primer estudio para evaluar la contaminación por PCB en aguas costeras de Costa Rica. En general, las concentraciones fueron bajas especialmente cuando se les compara con sedimentos de climas templados y / o sedimentos de areas altamente industrializadas. Los valores promedio son inferiores a 3 ng / dw (peso seco) de sedimento. Sin embargo, unas pocas muestras contienen hasta 7 ng/ g dw de sedimento. Los sedimentos con las concentraciones más altas están localizados en el area de Punta Morales, en cienos de entre raíces de mangle. Las concentraciones de PCB en Puntarenas fueron sorprendentemente bajas, posiblemente por el tipo arenoso del sustrato. La distribución de congéneres dentro de la mayoría de las muestras muestran señal de una reciente contaminación o carencia de degradación . Sin embargo, en unos pocos sitios, específicamente en las islas internas del Golfo y otras areas más remotas tienen distribuciones de congéneres que indican contaminación por vía aerea y /o degradación. Cuando se considera la presencia de PCB transportados por via aerea en el Golfo de Papagayo al Norte, es sorprendente la ausencia en el Golfo de Nicoya de estos PCB y una distribución más variada de congéneres